Heat Transfer Slot Matrix for Compact Rotary Heat Exchangers with Ultra-High Regeneration Ratio for Microturbines - Kostyukov A. V.; Kosach L. A. (Problems of the Regional Energetics)
This paper considers the problem of the influence of distancing elements in slot matrix channels on the thermohydraulic characteristics of the matrix of a rotary heat exchanger having various values of the height of the slot channels. The following tasks were carried out: mathematical modeling of thermohydraulic processes in different slot channels having constant height along them (from 0.3 mm to 0.5 mm); analysis of the influence of the slit channels' height, the number of distancing elements in rows, the distance between rows and the total number of elements on the average value of the Nusselt number and on the pressure drop; analysis of the effect of changes in speed and temperature conditions on thermal and hydraulic characteristics. The most important results are the following facts: the influence of the relative location of the distancing elements on the thermohydraulic characteristics of the flow is negligible; changes in the tempera-ture and speed regime of the laminar flow practically does not affect the intensity of convection in the matrix channels; an increase in the height of the slot channel leads to a relatively small decrease in the average value of the Nusselt number. The significance of the results obtained is that they can be the basis for adjusting the methods of design calculations of rotary heat exchangers taking into account the decrease in thermal effi-ciency caused by the presence of distancing elements in the channels of their matrices. Recom-mendations can be made to minimize the number of distancing elements without considering their mutual location.